Pelatihan Eksplorasi Mocktail Dengan Sentuhan Rempah Nusantara Bagi Kampung Adat Cireundeu Bandung - Gilang Fahreza; Lilik Edi Saputro (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Cireundeu Traditional Village is in Leuwigajah Village, South Cimahi District and has a population of 800 people. Most of the people in the Cireundeu Traditional Village work as cassava farmers and adhere to the Sundanese Wiwitan belief. The traditional potential must be supported by development, especially in the field of providing food and drinks that utilize village potential. Spices are a strong potential of the Cirendeu Traditional Village, they can come from various parts of plants, such as flowers, fruit, bark, stems, tubers, leaves and rhizomes. Spices can not only be used as seasonings for cooking, but can also provide taste, aroma and health benefits to various drinks. The Faculty of Economics and Business, Bina Sarana Informatics University Hospitality Study Program will hold community service with the theme "Mocktail exploration training with a touch of Indonesian spices for the Cirendeu Bandung Traditional Village". The community service partners are the Cirendeu Bandung Traditional Village community. This training activity is a solution for the potential of the Cirendeu Traditional Village. Counseling is carried out in 4 stages, namely; Preparation Stage, Implementation Stage, Monitoring and Evaluation Stage. Community service activities run smoothly and there are no obstacles. Several participants provided suggestions regarding implementation time, but considering the participants' enthusiasm for the community service material this time, some felt that the time was still not enough. The participants were very enthusiastic about taking part in the training and showed that they were very interested in making mocktail drinks with a touch of spices. The process of direct practice and reflection carried out by the instructors has helped them understand the correct steps for making mocktail drinks. This training also offers new business opportunities for participants who want to develop mocktail drinks with the added value of spices.